Native valve infective endocarditis due to Achromobacter xylosoxidans in an apparently immunocompetent individual. (29th November 2010) - Storey, Anna; Wilson, Anne; McWilliams, Eric
Abstract : A 79-year-old woman presented with fever, lethargy and weight loss. Clinically, the patient was confused, frail and had a systolic murmur. Her temperature was 38 °C and she remained persistently febrile. Initial investigations revealed neutrophilia with an elevated C reactive protein level. Multiple peripheral blood cultures grew Achromobacter xylosoxidans, a Gram-negative rod, which is a very rare cause of infection in patients who are immunocompetent. Subsequent transoesophageal echocardiography confirmed endocarditis with obvious vegetations on the mitral valve. The patient was treated with intravenous meropenem and cotrimoxazole in line with microbiology guidance. Surgical intervention in the form of mitral valve replacement was considered, but the patient was felt to be at prohibitive risk. After 6 weeks of intravenous antibiotics, a repeat transoesophageal echocardiogram showed no improvement in the mitral valve vegetation, which had increased in size. At this stage, her clinical course was complicated by major upper gastrointestinal bleeding requiring transfusion, multiorgan failure and ultimately death.